Extubation of patients with COVID-19 acute respiratory failure during extracorporeal membrane oxygenation support is associated with improved survival - Sean Kelleher; Christoph Brehm; Carol Dziedzina; Shouhao Zhou; Catherine Nashed; Ricarda White; Miriam Freundt; Octavio Falcucci; Amit Prasad (Exploration of Cardiology, 2025)
Aim: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or COVID-19, infection resulting in acute respiratory distress syndrome (ARDS) requiring veno-venous or veno-arterial extracorporeal membrane oxygenation (VV or VA-ECMO) support is a life-threatening disease process that requires prolonged intubation and has a high risk of mortality. Methods: In this retrospective, observational, single-center cohort study, we attempt to better understand the role of extubation in the course of treatment by dichotomizing groups into those extubated early while remaining on ECMO treatment (group A), compared to patients who remained intubated for the entirety of their ECMO treatment (group B). Results: The data indicate that early extubation of patients with COVID-19-associated ARDS requiring ECMO support leads to improved survival rates for group A (93%) compared to prolonged intubation (group B) throughout the course of ECMO therapy (64%) (p = 0.13). Additionally, patients extubated earlier (19 days vs. 59 days; p = 0.012) required significantly fewer vasoactive drugs (norepinephrine dosing: 0.03 mcg/kg/min vs. 0.093 mcg/kg/min; p = 0.04), and were less likely to require a tracheostomy (0 vs. 4, p = 0.026). Conclusions: Although the utility of ECMO in severe ARDS patients remains a contentious topic, early extubation seems to increase survival rates and overall patient outcomes in patients with COVID-19-associated ARDS requiring ECMO support.